MANAJEMEN LAYANAN BIMBINGAN DAN KONSELING DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA DI MADRASAH TSANAWIYAH NEGERI (MTsN) 1 JOMBANG - M. Al Kadafi; Muhammad Al-Fatih (JURNAL ILMIAH NUSANTARA, 2025)
Guidance and counseling service management is a process that involves planning, implementing, and evaluating various services provided to students in order to help them overcome the problems or challenges they face, whether in personal, social, academic, or career aspects. The focus of this research is: 1) How is the management of guidance and counseling services at MTsN 1 Jombang? 2) How is the academic achievement of students at MTsN 1 Jombang? 3) How is the Management of Guidance and Counseling Services in improving the Academic Learning Achievement of Students at MTsN 1 Jombang. The research method used is qualitative research with a descriptive case study research type. Data collection techniques used include observation, interviews, and documentation. Data reduction, data display, and conclusion drawing are the methods used for data analysis. Triangulation of sources, time, and techniques are used to ensure the authenticity of the data. The research results found by the researcher are: (1) The Guidance and Counseling service management plan to improve students' academic achievement must be stated in an activity schedule in the form of a calendar. The calendar consists of annual, semester, monthly, and weekly calendars. (2) The implementation of the Guidance and Counseling service management to improve students' academic achievement is carried out through observation, checklist preparation, interviews, and direct and indirect interactions. (3) Evaluation of the Guidance and Counseling service management in improving students' academic achievement is carried out in two ways, namely through the process and results. The process shows that handling individual services cannot always be completed quickly, because it takes time, while the results can be seen from the graduation rate; if the output is good, then its success can be said to be clear.